Locating Public Facilities: Theory and Micro Evidence from Paris - Gabriel Loumeau (Center for Economic Studies and Ifo Institute (CESifo), 2021)
This paper proposes a novel approach to evaluate location decisions for public facilities. The approach addresses, not only the standard distance-minimizing problem, but also the endogenous location decisions of individuals. To do so, I develop a quantifiable general equilibrium model with endogenous (residential and commercial) densities, housing prices, commutes to work and public facilities, as well as public facility characteristics. The latter includes a facility's location, quality, district and capacity. I apply the framework to secondary schools in Paris' greater region at a 1km2 geographical scale. The analysis reveals that the observed location decisions made between 2001 and 2015 underestimate the endogenous reaction of individuals. A more decentralized strategy is predicted to increase welfare growth by 10 percentage points on average, mostly via shorter commutes and lower housing prices.
Keywords: R53; H11; R12; 330; location; facility; general equilibrium; commuting; interrupted search